Efikasi diri dan media sosial: faktor penentu prokrastinasi akademik siswa sma - Permata, Rezha Anugrah; Matulessy, Andik; Suhadianto, Suhadianto (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2024)
Academic self-efficacy and intensity of social media use affect the level of academic procrastination. This study aims to determine the relationship between both with academic procrastination in high school students. Using a quantitative correlational method, this study involved 233 students of SMA X Surabaya with a purposive sampling technique. The results of the analysis showed a significant relationship between academic self-efficacy and intensity of social media use simultaneously with academic procrastination (F = 52.727; p = 0.000 < 0.05). Partially, there was a significant negative relationship between academic self-efficacy and academic procrastination, as well as between intensity of social media use and academic procrastination. These findings indicate that academic self-efficacy and intensity of social media use can be predictors of academic procrastination behavior in high school students.